The Theory of Planned Behavior for Predicting Muslim in Choosing the Qurban-Rendangmu Program - Wiwit Widhi Setiyawan; Indah Piliyanti (UIN Raden Mas Said Surakarta, 2026)
The purpose of this study was to examine the constructs of the Theory of Planned Behavior in the context of community behavior toward the qurban-rendangmu program.This study employs a quantitative research design. Data were collected through questionnaires distributed to 220 respondents, with measurement instruments using a five-point Likert scale. The data were analyzed using SmartPLS 3 software through Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The findings of this study indicate that attitude does not have a significant effect on the intention to perform qurban, but subjective norms and perceived behavioral control have a significant effect on the intention to perform qurban. These findings imply that strengthening social campaigns, involving community and persyarikatan leaders, and facilitating easy participation are more effective strategies than merely promoting individual attitudes toward the program.